Inner-shell photodetachment from Ni− : A giant Feshbach resonance - Dumitriu, I.; Bilodeau, R. C.; Gorczyca, T. W.; Walter, C. W.; Gibson, N. D.; Rolles, D.; Pešić, Z. D.; Aguilar, A.; Berrah, N. (My University, 2017)
Inner-shell photodetachment from Ni−([Ar]3d94s2) leading to Ni+,Ni2+, and Ni3+ ion production was studied near and above the 3p excitation region, in the 60–90 eV photon energy range, using a merged ion-photon beam technique. The absolute photodetachment cross section of Ni− leading to Ni+ ion production was measured. The 3p→3d photoexcitation in Ni− gives rise to a giant Feshbach resonance. In the near-threshold region, a Fano profile, modified by a Wigner s-wave (l=0) threshold law, accurately fits the Ni− single-photodetachment cross section. A lower-order R-matrix calculation shows overall agreement with essential features of the experimental data, confirming the nature of the strong, asymmetric Fano profile of the giant 3p→3d photoexcitation-autodetachment resonance in Ni−.
Citation: Dumitriu, I., Bilodeau, R. C., Gorczyca, T. W., Walter, C. W., Gibson, N. D., Rolles, D., … Berrah, N. (2017). Inner-shell photodetachment from $\mathrm{N}{\mathrm{i}}^{\ensuremath{-}}$: A giant Feshbach resonance. Physical Review A, 96(2), 023405. https://doi.org/10.1103/PhysRevA.96.023405
Keywords: Photodetachment; Atomic, Molecular & Optical